Cytomegalovirus-associated encephalomyelitis in an immunocompetent adult: a two-stage attack of direct viral and delayed immune-mediated invasions. case report - Daida, Kensuke (BMC Neurol, 2016)
BACKGROUND: It is clinically rare to find cytomegalovirus (CMV)-associated encephalomyelitis in immunocompetent adults. Here, we present the case of an adult patient who developed acute transverse myelitis that was followed by immune-mediated disseminated encephalomyelitis. CASE PRESENTATION: A 38-year-old man developed acute paraplegia with paresthesia below the level of the T7-8 dermatome. Both brain and spinal cord MRIs performed at admission appeared normal. Corticosteroid therapy was initiated, with the later addition of high-dose intravenous immunoglobulins. After polymerase chain reaction analysis indicated the presence of CMV DNA in his cerebrospinal fluid (CSF), anti-viral therapy was added. Forty days after symptom onset, despite an initial positive response to this therapy, he developed dysarthria and truncal ataxia. Repeated magnetic resonance imaging scans demonstrated progressively expanding lesions involving not only the spinal cord but also the cerebral white matter, suggestive of extensive immune-mediated demyelination involving the central nervous system (CNS), as is observed in acute disseminated encephalomyelitis (ADEM). CONCLUSION: This case report underscores the importance of careful patient observation following the initial diagnosis of a CMV-associated CNS infection, such as transverse myelitis, on the possibility that post-infectious ADEM may appear.